2017
DOI: 10.1007/s00296-017-3893-0
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease in South Africans with systemic sclerosis

Abstract: BACKGROUND: Interstitial lung disease (ILD) is one of the leading causes of death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Information on silica exposure was not available in 92% of study subjects, but was reported in 141 patients [8%] [ 4 , 45 , 48 , 49 , 91 , 92 ] which were mostly miners. Only 5 patients [0.3%] were reported to be free of silica exposure [ 14 , 21 , 50 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
See 3 more Smart Citations
“…Information on silica exposure was not available in 92% of study subjects, but was reported in 141 patients [8%] [ 4 , 45 , 48 , 49 , 91 , 92 ] which were mostly miners. Only 5 patients [0.3%] were reported to be free of silica exposure [ 14 , 21 , 50 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…The presence or absence of telangiectasia was documented in 321 patients [17%] of all patients]); in whom telangiectasia were present in 73 patients [23%]. In the publication with the most representative data, telangiectasia were present in only 19 of 151 patients [13%] [ 49 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Anti-Ku patients with elevated creatine-kinase at baseline may develop ILD and a diagnosis of SSc and not myositis [ 29 ], mainly, but not exclusively, in patients with diffuse SSc and with a speckled ANA pattern. Conversely, the presence of anti-centromere was considered protective against ILD as already mentioned [ 30 ]. Additional autoAbs associated with the risk of ILD in SSc include anti-RP11 and anti-NOR90, in particular in male patients [ 31 ], while patients with isolated SSc-PH are less likely to have anti-Scl70/topoI autoAbs and they are more prone to be ACA positive.…”
Section: Autoabs Associated With Ild In Sscmentioning
confidence: 99%